Politeness Strategies in Lecturers’ Written Corrective Feedback: A Discourse Analysis in Indonesian EFL Higher Education - Asmida Yanti Siregar; Didin Nuruddin Hidayat; Nida Husna (FOSTER: Journal of English Language Teaching, 2026)
Previous research has explored politeness strategies in contexts such as classroom interactions and online communication; however, further investigation across diverse dimensions of educational discourse is necessary. This study examines the politeness strategies utilized by lecturers when delivering Written Corrective Feedback (WCF) to undergraduate EFL students in Indonesia. This research adopted a descriptive qualitative research design comprising data from twelve files of WCF collected from the Contrastive Error Analysis course at a public university in Indonesia. Discourse-based coding was employed to analyze the data, identifying the four maxims of politeness theory: positive politeness, negative politeness, off-record strategies, and bald-on-record expressions. The findings showed that the lecturer applied all four politeness strategies; furthermore, positive and negative politeness were the most frequently used. Positive politeness was expressed through praise, encouragement, and inclusive language to enhance students' confidence, whereas negative politeness was demonstrated through hedging, indirect suggestions, and question forms that maintained student autonomy. Off-record strategies primarily addressed higher-order issues, including coherence and argumentation, while bald-on-record strategies were limited to surface-level corrections. The findings enhance the understanding of feedback discourse and provide implications for improving feedback practices in EFL contexts, especially within Indonesian higher education.